1999
DOI: 10.1159/000054490
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Innervation and Neuropeptide-Y-Y1-Receptor-Expressing Neurons in the Paraventricular Hypothalamic Nucleus of the Mouse

Abstract: The paraventricular hypothalamic nucleus (PVH) serves as integrator and link between the neuroendocrine and autonomic nervous systems. Neuropeptide-Y (NPY)-producing neurons in the arcuate nucleus project to the PVH, where neurons expressing NPY Y1 receptor (Y1R) have been demonstrated. This projection has been suggested to be involved in the regulation of parameters related to energy metabolism, e.g. food intake and thermoregulation. The present study aimed at characterizing this pathway and chemically defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 58 publications
5
66
2
Order By: Relevance
“…Conversely, several lines of evidence have demonstrated that acute activation of arcuate NPY neurons stimulates the HPA axis through activation of the CRF system (Wahlestedt et al 1987;Dallman et al 1993). CRF neurones in the PVN are direct targets of NPY neurons (Wahlestedt et al 1987;Liposits et al 1988;Li et al 2000) and acute central Restraint and Y1 receptor gene expression 1475 administration of NPY increases CRF expression and secretion in the hypothalamus (Haas and George 1987;Grossman et al 1993;Suda et al 1993;Blasquez et al 1995), possibly by activation of the Y 5 receptor subtype (Broberger et al 1999;Campbell et al 2001). In addition, CRF neurones in the PVN are contacted by fibres that express the Y 1 receptor, suggesting that NPY might indirectly activate the CRF neurons by acting on presynaptic Y 1 receptors (Li et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, several lines of evidence have demonstrated that acute activation of arcuate NPY neurons stimulates the HPA axis through activation of the CRF system (Wahlestedt et al 1987;Dallman et al 1993). CRF neurones in the PVN are direct targets of NPY neurons (Wahlestedt et al 1987;Liposits et al 1988;Li et al 2000) and acute central Restraint and Y1 receptor gene expression 1475 administration of NPY increases CRF expression and secretion in the hypothalamus (Haas and George 1987;Grossman et al 1993;Suda et al 1993;Blasquez et al 1995), possibly by activation of the Y 5 receptor subtype (Broberger et al 1999;Campbell et al 2001). In addition, CRF neurones in the PVN are contacted by fibres that express the Y 1 receptor, suggesting that NPY might indirectly activate the CRF neurons by acting on presynaptic Y 1 receptors (Li et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This change likely has important effects on the hypothalamopituitary thyroid axis, as NPY, AgRP, and α-MSH-containing neuronal endings have been detected in close association with neurons in the PVN that synthesize thyrotropin-releasing hormone (TRH) in rodents (Legradi and Lechan, 1999) and in humans . Moreover, TRH-expressing neurons in the PVN of the mouse are known to express Y1 receptor-like immunoreactivity (Broberger et al, 1999). Unlike the MC3 receptor, MC4 receptor mRNA (Mountjoy et al, 1994) as well as Y1 and Y5 receptor immunoreactivity (Wolak et al, 2003) are found in both parvicellular and magnocellular neurons of the PVN as recently reviewed , suggesting direct effects of NPY and melanocortins on the thyrotropic axis at the level of the hypothalamus.…”
Section: Preston Et Almentioning
confidence: 97%
“…On the other hand, the arcuate nucleus neuropeptide Y/agouti-related protein (NPY/AgRP) system, which Cota et al demonstrate is not directly targeted by endocannabinoid action, appears to be a less critical (or a functionally more redundant) player in the chronic maintenance of energy balance (17). However, disruption of NPY Y1 or Y2 receptors, which are intricately related to some of the peptidergic neurons (18)(19)(20)(21) that are shown by Cota et al to express CB1 receptors, attenuate the development of type 2 diabetes (22,23).…”
Section: Figurementioning
confidence: 99%